Efektivitas Metode Tanya Jawab dalam Pembelajaran Akidah Akhlak dalam Meningkatkan Motivasi Belajar dan Kemampuan Berpikir Kritis Peserta Didik Kelas X di MA Hasyim Asy’ari Jogoroto Jombang - Fathur Rofi'i; Zainul Arifin; Zainul Abidin (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2026)
ABSTRACT This study aims to determine the effectiveness of the question-and-answer method in teaching Akidah Akhlak (Islamic Creed) in improving learning motivation and critical thinking skills in 10th-grade students at MA Hasyim Asy'ari Jogoroto, Jombang. This study is a qualitative study using a descriptive approach. Data collection techniques included observation, questionnaires, interviews, and essay tests. The data analysis technique used Huberman and Mils' triangulation, which begins with data reduction, data presentation, and data verification or drawing conclusions. The results showed that the average student learning motivation, based on the questionnaire, reached 82.06 (very high) and based on observations, 59.8 (sufficient), with a combined average score of 70.93 (high). For critical thinking skills, the average class score was 73.13 (good category), with the following breakdown: assumptions and conclusions received excellent scores (86.67%), while argumentation, deduction, and interpretation received scores of 70%, 63.33%, and 53.33%, respectively. This research shows that the question-and-answer method is effective in increasing students' learning motivation and critical thinking skills. Active interaction between teachers and students, as well as the use of media such as images and videos, can encourage deeper student engagement. Keywords: Question-and-Answer Method, Learning Motivation, Critical Thinking